The Relationship Between The Level Of Knowledge And The Implementation Of Early Mobilization On Wound Healing In Post-Caesarean Section Mothers At The Kotamobagu City Hospital. - Dinalisnawaty Akri Daeng Maeta; Widia Shofa Ilmiah (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2025)
The healing process of incisional wounds after cesarean section (SC) surgery is a multifactorial outcome influenced by both cognitive and behavioral aspects, particularly the mother's level of knowledge and the implementation of early mobilization. Early mobilization is proven to accelerate tissue repair by enhancing physiological recovery mechanisms, yet its effectiveness highly depends on the mother’s understanding and willingness to initiate movement postoperatively. This study aims to examine the relationship between knowledge level and early mobilization practices on wound healing outcomes among post-SC mothers at the Regional Public Hospital (RSUD) of Kota Kotamobagu. A quantitative analytic study was conducted using a cross-sectional design, involving 40 respondents selected through total sampling. Data were collected via structured questionnaires and clinical observation of wound healing on the third postoperative day. Statistical analyses included Chi-Square tests and multivariate logistic regression. The results showed that all mothers with low knowledge or poor mobilization practices experienced delayed wound healing, whereas those with moderate to high knowledge and proper mobilization demonstrated optimal recovery. A p-value of 0.000 was obtained for both variables, indicating a highly significant relationship. Early mobilization was the strongest predictor of wound healing success (OR = 25.98), followed by good knowledge levels (OR = 8.52). The study concludes that both knowledge and early mobilization behavior significantly contribute to postoperative recovery in SC patients. Educational reinforcement and psychosocial support during hospitalization are essential to promote early mobilization practices and empower mothers in participating actively in their healing process.